WEIGHTED STATISTICAL CONVERGENCE OF ORDER cx IN PROBABILITY - Akbas, Kubra Elif; Isik, Mahmut (Inst Mathematics & Mechanics, Natl Acad Sciences Azerbaijan, 2025)
In this study, we introduce and examine the concepts of weighted statistical convergence of order cx and weighted [Np]-summability of order cx in probability. Also some relations between weighted statistical convergence of order cx and weighted [Np]-summability of order cx in probability are given.
Keywords: statistical convergence; sequences of random variables; Cesaro summability; statistical convergence of order alpha; weighted statistical convergence